The Changing Governance of the Sciences
XIV, 166 p.
Keywords: The establishment of national systems of retrospective research evaluations is one of the most significant of recent changes in the governance of science. In many countries, state attempts to manage public science systems and improve their quality have triggered the institutionalisation of such systems, which vary greatly in their methods of assessing research performance, and consequences for universities. The contributions to this volume discuss, inter alia, the birth and development of research evaluation systems as well as the reasons for their absence in the United States, the responses by universities and academics to these new governance regimes, and their consequences for the production of scientific knowledge. By integrating new theoretical approaches with country studies and studies of general phenomena such as university rankings and bibliometric evaluations, the book shows how these novel state steering mechanisms are changing the organisation of scientific knowledge production and universities in different countries. In combining latest research and an overview of trends in the changing governance of research, the book is essential not only for scholars engaged in higher education research, science policy studies, and the sociology of science but also for policy makers and analysts from science policy and higher education policy as well as university managers and senior scientists. .